Macroeconomic dynamics in a model of goods, labor and credit market frictions - Nicolas Petrosky-Nadeau; Etienne Wasmer (Institute for the Study of Labor (IZA), 2011)
Building a model with three imperfect markets - goods, labor and credit - representing a product's life-cycle, we find that goods market frictions drastically change the qualitative and quantitative dynamics of labor market variables. The calibrated model leads to a significant reduction in the gap with the data, both in terms of persistence and volatility while search models of the labor market fail in one of the two dimensions. Two factors related to goods market frictions generate these results: i) the expected dynamics of consumers' search for goods, itself depending on the income redistributed by firms and the entry of new products; and ii) the expected dynamics of prices, which alter future profit flows.
urn:nbn:de:101:1-201106202182
Keywords: J6; E12; E13; E3; 330; search; matching; business cycle; goods market imperfection